Factores de riesgo y su influencia en la adherencia de los pacientes al tratamiento antituberculosos. Hospital Jaime Roldos Cantón Ventanas, Los Ríos. Septiembre 2017 – febrero 2018 - Zapata Aguirre, Johanna Maricela (2018)
Tuberculosis is an infectious disease in various countries of the world, taking into account that the prevention and cure of this disease is the main objective of public health. In this disease, contagion occurs more frequently in the home, favored by ignorance, lack of schooling, low economic resources, untimely medical attention, lack of support in this chronic disease, causing in some cases the abandonment of treatment, further complicating the patient's situation and favoring drug resistance and consequently the prevalence of infection. The objective of this research was to identify the factors that influence patients' abandonment and adherence to antituberculous treatment and thus establish a proposal to improve comprehensive care for patients included in the Tuberculosis Control Program. causing your health situation to improve considerably. The design of the study was explorative, descriptive, explanatory. The population and sample in which they studied were 14 cases of tuberculous patients, between those who adhered to the treatment and those who left it. The data obtained was a survey of 10 questions to patients with adherence and abandonment to treatment were through the application of a structured instrument through the technique of interviewing the patient, and their families.